Pengaruh Pelayanan Dan Fasilitas Terhadap Kepuasan Peserta Kegiatan MICE Di UNP Hotel & Convention Center - Fhareldo S. Dillivio; Trisna Putra (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This research aims to determine the satisfaction of MICE participants at the UNP Hotel & Convention Center. This research focuses on MICE activities in the form meeting and conference. This research is entitled The Influence of Services and Facilities on the Satisfaction of Participants in MICE at the UNP Hotel & Convention Center. The data collection technique for this research is indirect communication by distributing questionnaires with a Likert scale to meeting and conference participants then the data processed using the SPSS program. This research is a quantitative descriptive with a causal associative approach. The population of this study were people who had participated in meeting and conference activities at the UNP Hotel & ConventionCenter in the period July-December 2022 with a sample of 98 people, and the sampling technique was non-probability sampling with a minimum age of 18 years. There are 2 types of data used in this research, namely primary data and secondary data. The results of this research show that service is in the very good category (80,61%), facilities are in the very good category (74,50%), and participant satisfaction is in the very satisfied category (87,75%). It was found that the R square value was 0.464 with an F count of 41,072 and a significance level of 0.000<0.05 and the t value was 11,529 with a significance level of 0.000<0.05 meaning that variable X influenced variable Y significantly by 46.4%. It was found that the regression coefficient value of the service variable was 0.346 with a significance of 0.000<0.05, which means that every increase of 1 unit of service will increase participant satisfaction by 0.346 units of satisfaction, and the coefficient value of the facility variable was 0.530 with a significance of 0.000<0.05, which means every increase of 1 facility units will increase participant satisfaction by 0.530 satisfaction units.